The Impact of Entrepreneurial Characteristics on the Success of Online Fresh Produce Businesses in Medan - Chyntia Winata Luis; Sri Ariani Safitri; Rika Fitri Ilvira (Jurnal AGRISEP, 2025)
This research aims to analyze entrepreneurial characteristics, business success, and the influence of entrepreneurial characteristics on business success. The number of samples in this research was 38, using a purposive sampling method. The research results show that the average score level on the entrepreneurial characteristics indicator is 148.8, with a percentage of 78.2% (high category). Not only that, but business success also has an average score of 134.3 with a rate of 70.6% (high category), and there is a significant influence between Entrepreneurial Characteristics (KW) and Business Success (KU). The t-statistical value of Entrepreneurial Characteristics (KW) on Business Success (KU) is 28.476, more significant than the t-table 1.68. This means there is a substantial difference of 28.476 between the average of the two variables and the relationship between them. Apart from that, the resulting research p-value of 0.000 is smaller and much lower than the alpha value (0.05), which means it is significant and rejects H0. The suggestions in this research are for online fresh fruit and vegetable business actors to improve their management skills and strategies in running their businesses and further improve strategies in utilizing the technology used in promotions to attract customer attention. Buy and be better able to market their products inside and outside the city by becoming entrepreneurs. Entrepreneurial characteristics have a significant influence on business success.